A perioperative consult service results in reduction in cost and length of stay for colorectal surgical patients: evidence from a healthcare redesign project. Issue 1 (December 2016) - McEvoy, Matthew; Wanderer, Jonathan; King, Adam; Geiger, Timothy; Tiwari, Vikram; Terekhov, Maxim; Ehrenfeld, Jesse; Furman, William; Lee, Lorri; Sandberg, Warren
Abstract Background A major restructuring of perioperative care delivery is required to reduce cost while improving patient outcomes. In a test implementation of this notion, we developed and implemented a perioperative consult service (PCS) for colorectal surgery patients. Methods A 6-month planning process was undertaken to engage key stakeholders from surgery, nursing, and anesthesia in a healthcare redesign project that resulted in the creation of a PCS to implement a coordinated clinical pathway. After Institutional Review Board (IRB) approval, data were collected for all elective colorectal procedures for three phases: phase 0 (pre-implementation; 1/2014–6/2014), phase 1 (7/2014–10/2014), and phase 2 (11/2014–10/2015). Length of stay (primary endpoint; LOS), total hospital cost, use of clinical pathway components, markers of functional recovery, and readmission and reoperation rates were analyzed. Outcomes and patient characteristics among phases were compared by two-tailedt tests and Wilcoxon rank-sum tests. Categorical variables were analyzed by chi-square and Fisher's exact tests. Results We studied 544 patients (phase 0 = 179; phase 1 = 124; phase 2 = 241), with 365 consecutive patients being cared for in the redesigned care structure. Median LOS was reduced and sustained after implementation (phase 0, 4.24 days; phase 1, 3.32 days; phase 2, 3.32 days, P  < 0.01 phase 0 v. phases 1 and 2), and mean LOS was reduced in phase 2 (phase 0, 5.26 days; phase 1, 4.93 days; phase 2, 4.36 days, P  < 0.01 phase 0 v. phase 2). Total hospital cost was reduced by 17 % (P  = 0.05, median). Application of clinical pathway components was higher in phases 1 and 2 compared to phase 0 (P  < 0.01 for all components except anti-emetics); measures of functional recovery improved with successive phases. Reoperation and 30-day readmission rates were no different in phase 1 or phase 2 compared to phase 0 (P  > 0.15). Conclusions Restructuring of perioperative care delivery through the launch of a PCS-reduced LOS and total cost in a significant and sustainable fashion for colorectal surgery patients. Based on the success of this care redesign project, hospital administration is funding expansion to additional services.